2010
DOI: 10.1158/1078-0432.ccr-09-2328
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy for Advanced Non-small Cell Lung Cancer: Current Status, Controversies, and Emerging Consensus

Abstract: Maintenance therapy refers to the use of an active therapeutic agent for extended duration following frontline induction therapy for patients with advanced stage non-small cell lung cancer (NSCLC). Multiple clinical trials reported within the last few months have shown a beneficial role for maintenance therapy especially in select patient groups characterized by histology and/or molecular profile. With the recent approval by the U.S. Food and Drug Administration and European Medicines Agency of pemetrexed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…27 Therefore, although improvements in PFS have been often reported with maintenance/ consolidation chemotherapy, significant advantages in terms of OS have not been obtained. 28 Based on our findings and on the promising data of previous studies, we deem it reasonable to believe that the encouraging results observed in the current study in terms of PFS and OS might be because of the combination of oral E and Bev as maintenance treatment. The median OS of the 13 patients who were able to receive second-line treatment was 13.8 months, and did not seem to have an effect on the ultimate median and 1-year survival of the group.…”
Section: Discussionsupporting
confidence: 63%
“…27 Therefore, although improvements in PFS have been often reported with maintenance/ consolidation chemotherapy, significant advantages in terms of OS have not been obtained. 28 Based on our findings and on the promising data of previous studies, we deem it reasonable to believe that the encouraging results observed in the current study in terms of PFS and OS might be because of the combination of oral E and Bev as maintenance treatment. The median OS of the 13 patients who were able to receive second-line treatment was 13.8 months, and did not seem to have an effect on the ultimate median and 1-year survival of the group.…”
Section: Discussionsupporting
confidence: 63%
“…Systemic combination chemotherapy is considered the standard of care for patients with advanced NSCLC despite intense efforts at modifying treatments toward improving survival outcomes [3]. The use of standard chemotherapy is restricted to a defined number of cycles, as continuation results in added toxicity without meaningful improvements in progression-free or overall survival [27]. The addition of a third cytotoxic agent to the two-drug combination has been evaluated, however no differences in efficacy were seen and the toxicity profile worsens [28].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, several prospective phase 3 trials and meta-analyses of previously published data have suggested the potential benefits associated with maintenance therapy in cancer management [9][10][11][12][13][14][15][16][17]. Table 1 lists a number of such studies, and briefly summarizes their overall results.…”
Section: Recent Evidence Supporting the Utility Of "Maintenance Theramentioning
confidence: 99%
“…However, relatively recently reported data have begun to challenge the concept that optimal disease management necessitates stopping systemic antineoplastic therapy in a responding or clinically stable (nonprogressing) cancer patient, and have suggested that a "maintenance" strategy may be appropriate in at least some well-defined clinical settings [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%